Narrow distance inter-pregnancies increase the incidence of Post-Partum hemorrhage - Nadhira Farah Puspitasaria; Rachmiyani, Irmiya (Sanus Medical Journal, 2022)
Background and Aims. Maternal Mortality Rate (MMR) is the parameters of women's health status in community. The single most common cause of maternal mortality is obstetric haemorrhage, generally occurring postpartum. Most postpartum haemorrhage cases are caused by uterus atony, myometrium tonus loss, placenta retention, and clotting disorders. Short pregnancy intervals can cause threefolds of anaemia than normal pregnancy intervals. Pregnant women who suffer from anaemia has the possibility experiencing a postpartum bleeding caused by atonia uteri. This research aims to acknowledge the effect of narrow distance interpregnancy on a postpartum haemorrhage. Methods. This study uses an observational analytic study with a cross"‘sectional design. The data used is secondary data of pregnant women based on medical record to calculate the distance of interpregnancy with the incidence of postpartum bleeding during childbirth at Budhi Asih General Hospital of East Jakarta. The inclusion criteria are women who underwent childbirth during 2017"‘2018, multiparity, and postpartum women between 20"‘35 years old. The exclusion criteria are women with a history of postpartum haemorrhages caused by placental retention, tear of the reproductive tract or blood coagulation), gemelli parturition, macrosomia, assisted childbirth, grande multiparity, induction childbirth, and dystocia. Results. The number of samples used in this study amounted to 111 people. Postpartum haemorrhage are significantly associated with short interpregnancy intervals (p=0,000). Conclusion. Narrower pregnancy interval will leads to postpartum haemorrhage. To prevent this, it is important to consider contraception utilization, to improve iron consumption for pregnant women, and to provide decent antenatal care.